2B or Not 2B Plurilingual? Navigating Languages Literacies, and Plurilingual Competence in Postsecondary Education in Canada. Issue 3 (16th August 2013) - Marshall, Steve; Moore, Danièle
<x xml:space="preserve">Abstract</x> In this article, the researchers employ the framework of plurilingualism and plurilingual competence in a field that has traditionally been dominated by reified conceptualizations of multilingualism that view bi/multilingualism as balanced and complete competence in discrete codes. They present data from a qualitative, longitudinal study of the interplays between the social, cultural, and linguistic in the multiple languages and literacy practices of transnational students at a university in Vancouver, Canada. Their findings question the role of academic English as the sole conduit to success for participants in higher education. They suggest that this relates back to how plurilingualism is defined and integrates the key idea that learning skills, multilingual literacies, (inter)cultural experiences, and different forms of knowledge are transferable and thus constitute assets and tools for better learning (Castellotti & Moore, 2010; Coste, Moore, & Zarate, 1997). Participants revealed a considerable degree of fluidity in their languages and literacy practices as well as shifts in perceptions and practice that change according to context. They proved to be highly plurilingual, reflexively and knowledgeably (Giddens, 1984) moving from contexts in which they mixed different languages and scripts freely to contexts in which they adhered to more normative senses of discrete monolingual practices in English and community languages.